The Effect of Patient-Centered Communication and Racial Concordant Care on Care Satisfaction Among U.S. Immigrants. (August 2021) - Chu, Jun; Wang, Nianyang; Choi, Yoon Soon; Roby, Dylan H.
Immigrants living in the United States experience disparities in satisfaction with medical care. Practicing patient-centered communication and providing racially (or race-concordant) concordant care are suggested as effective approaches to improve care satisfaction. Using the Medical Expenditure Panel Survey, we found that immigrant patients with medical providers who practiced patient-centered communication were more likely to be satisfied with the care they received regardless of patient–provider racial concordance, and that simply having racially concordant medical providers did not significantly affect the satisfaction level for immigrant patients. The findings suggest that providing patient-centered communication may mitigate racial and cultural differences between providers and patients, and is key to reducing disparities and improving immigrant patients' satisfaction level with medical care.